Free oscillation rheometry monitoring of haemodilution and hypothermia and correction with fibrinogen and factor XIII concentrates. - Winstedt, Dag; Tynngård, Nahreen; Olanders, Knut; Schött, Ulf (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine, 2013)
Haemodilution and hypothermia induce coagulopathy separately, but their combined effect on coagulation has not been widely studied. Fibrinogen concentrate can correct dilutional coagulopathy and has an additional effect when combined with factor XIII concentrate. However, their effect on dilutional coagulopathy concomitant with hypothermia has not been studied previously. Free oscillation rheometry - FOR (Reorox®) - is a novel viscoelastic haemostatic assay that has not been studied in this context before.
Keywords: concentrate; Coagulation factor; Free oscillation rheometry; Thrombelastography; Fibrinogen; Factor XIII; Haemodilution; Hypothermia; Coagulopathy; Hydroxyethyl starch; Ringer's acetate solution